2017
DOI: 10.1093/hmg/ddx205
|View full text |Cite
|
Sign up to set email alerts
|

Primary congenital and developmental glaucomas

Abstract: Glaucoma is the leading cause of irreversible blindness worldwide. Although most glaucoma patients are elderly, congenital glaucoma and glaucomas of childhood are also important causes of visual disability. Primary congenital glaucoma (PCG) is isolated, non-syndromic glaucoma that occurs in the first three years of life and is a major cause of childhood blindness. Other early-onset glaucomas may arise secondary to developmental abnormalities, such as glaucomas that occur with aniridia or as part of Axenfeld-Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 97 publications
0
78
0
12
Order By: Relevance
“…7 Esta anomalía abarca una serie de trastornos tanto oculares como sistémicos, 12 puede presentarse con anomalías presentes particularmente en el iris, la córnea y en la cámara angular. Este proceso usualmente es bilateral 13 como en el caso de la paciente en la cual se evidencia la presencia de un embriotoxon en ambos ojos.…”
Section: Discussionunclassified
“…7 Esta anomalía abarca una serie de trastornos tanto oculares como sistémicos, 12 puede presentarse con anomalías presentes particularmente en el iris, la córnea y en la cámara angular. Este proceso usualmente es bilateral 13 como en el caso de la paciente en la cual se evidencia la presencia de un embriotoxon en ambos ojos.…”
Section: Discussionunclassified
“…To improve understanding of how genes associated with glaucoma contribute to disease pathogenesis, we mapped their expression by the 19 cell types in our atlas. We included both known monogenic causes (Mendelian genes) and genes implicated as risk factors in GWAS studies (Wiggs and Pasquale, 2017;Lewis et al,2017;Choquet et al, 2018;Gao et al, 2018;Khawaja et al, 2018;Macgregor et al, 2018;Sears et al, 2019;Youngblood et al, 2019;Krumbiegel et al,2019). Mendelian genes assessed were ANGPT1, ANGPT2,CPAMD8,CYP1B1,FOXC1,LOXL1,LTBP2,MYOC,OPTN,PITX2,TEK (TIE2), and TBK1.…”
Section: Cell-type Specific Expression Patterns Of Glaucoma-associatementioning
confidence: 99%
“…We then used this cell atlas in two ways. First, we assessed expression in each cell type of genes that have been implicated in glaucoma, either as causal genes with Mendelian inheritance or as susceptibility loci identified in genome-wide association studies (GWAS) (Wiggs and Pasquale, 2017;Lewis et al,2017;Choquet et al, 2018;Gao et al, 2018;Khawaja et al, 2018;Macgregor et al, 2018;Sears et al, 2019;Youngblood et al, 2019;Krumbiegel et al,2019), and compared expression levels in cell types of the outflow pathways to those in retinal RGCs and retinal glia (Yan et al, in prep). We found that genes associated with elevated IOP were more likely to be preferentially expressed in the anterior segment, whereas those associated with normal tension glaucoma were more likely to be expressed predominantly in the retina.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, although ANGPT2 is largely reported to be an endothelialspecific gene that is induced in response to hypoxia, inflammation, and growth factor signaling (16), Kim et al documented high levels of ANGPT2 in TM cells, raising the mechanistic question of how these highly specialized cells activate ANGPT2 expression. Finally, in addition to TIE2, several other causative genes responsible for PGC, such as CYP1B1 and LTBP2, have been identified, but their mechanism of action is so far unclear (22). It will be therefore important to investigate how TIE2/ERK/PROX1 signaling intersects with other PGC genes in the regulation and maintenance of SC function.…”
Section: Schlemm's Canal: a Hybrid Vessel Important For Aqueous Outflowmentioning
confidence: 99%